2013
DOI: 10.1063/1.4821154
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ion dynamics with characteristic length scales and network structural units in bismuth borate glasses

Abstract: Ion dynamics in lithium bismuth borate conducting glasses have been reported in wide composition and temperature ranges. The activation energy for the dc conduction has been analysed using Anderson-Stuart model and a correlation between the dc conductivity and the doorway radius has been predicted. The characteristic length scales for ion dynamics, such as mean square displacement and spatial extent of sub-diffusive motion of lithium ions have been determined from the ac conductivity and dielectric spectra, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
1
13
1
Order By: Relevance
“…[30][31][32][33][34][35] Additionally, there has been some efforts in extracting relevant length scales (see Appendix A) by analyzing the ionic conductivity and dielectric permittivity spectra in alkali ion based MGF systems. 17,[36][37][38] The main findings on changes in structural units and bonds as a function of relative composition of glass formers in borophosphate glasses containing Li2O or Na2O as network modifiers is that hetero-atomic bonds such as P-O-B are preferred to homo-atomic bonds such as P-O-P and B-O-B, for up to about 30 mol% borate content. This information was made possible by X-Ray Diffraction (XRD) technique and XPS spectroscopy, 27 or by using Raman and magic-angle spinning (MAS) NMR experiments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[30][31][32][33][34][35] Additionally, there has been some efforts in extracting relevant length scales (see Appendix A) by analyzing the ionic conductivity and dielectric permittivity spectra in alkali ion based MGF systems. 17,[36][37][38] The main findings on changes in structural units and bonds as a function of relative composition of glass formers in borophosphate glasses containing Li2O or Na2O as network modifiers is that hetero-atomic bonds such as P-O-B are preferred to homo-atomic bonds such as P-O-P and B-O-B, for up to about 30 mol% borate content. This information was made possible by X-Ray Diffraction (XRD) technique and XPS spectroscopy, 27 or by using Raman and magic-angle spinning (MAS) NMR experiments.…”
Section: Introductionmentioning
confidence: 99%
“…[62][63] If the Haven ratio is assumed to be unity, since this is a hard to determine quantity, what this relation yields is < R 2 ( ) >, the mean-square displacement of the center of charge of the mobile ions. One thus constructs a plot of 〈R 2 ( )〉 versus log(t), and can read off the value of Another length scale which is relevant is the spatial extent of localized diffusion, and is calculated as 〈r 2 (∞)〉 1/2 from scaling of the real part of the permittivity spectra 7,45,46 using the MIGRATION concept; or in a model independent way from an analysis of the permittivity spectra 36,38,62,63 as 〈R 2 (∞)〉 1/2 . This length scale gives information on the nature of the localized excursions that the ion makes, and hence is closely related to local structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Though no specific correlation is identified between the σ dc conductivity and <R 2 (t p )>, the observed high ionic conductivity for NAPS-7.5 glass can be explained considering the highest <R 2 (t p )> value observed for the same glass. It has been reported for several glass compositions that the increase in the concentration of non-bridging oxygen decreases the <R 2 (t p )> as a consequence increases the dc-conductivity (Shaw and Ghosh, 2013;Chatterjee et al, 2020). On the contrary, it has also been identified that the increase in <R 2 (t p )> increases the dcconductivity due to structural modifications in the network structure of glass (Sklepić et al, 2021).…”
Section: Structure and Conductivity Correlation Through The Characteristic Displacement Curvesmentioning
confidence: 99%
“…The electrostatic binding energy (E b ) is the energy required to remove a mobile cation from its non-bridging oxygen site and is given by the following relation [27,28] (3)…”
Section: Si and 7 LI Solid-state Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%